Empowerment of Posyandu Cadres in Assisting Infant Massage at Fatululi Pustu, Kupang City - Mariana Ngundju Awang; Yurissetiowati Yurissetiowati; Melinda R Wariyaka (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
One form of growth and development stimulation that has been carried out by the community is by doing baby massage. Baby massage has many advantages, including reducing the habit of crying, gaining weight, making it easier for babies to sleep, practicing eye contact with the mother, reducing the baby's hormone stress level. The purpose of community service activities is to increase knowledge and skills of baby massage practice for Posyandu cadres and increase baby's weight and sleep quality. Materials used; phantom, questionnaire and internet quota.The methods are Pretest, Giving Materials through Lectures, Discussion/Question, Video screening and Posttest Followed by demonstrations, redemonstrations and direct massage practice on babies to improve Baby Massage Practice Skills. Results: Knowledge of baby massage before and after being given material with an assessment using the same instrument resulted in an increase in knowledge from a value of 50 to an average value of 80 values ??(minimum 70, maximum 90). Baby massage practice skills also increase along with the increase in knowledge so that it has an impact on weight gain and better sleep quality in babies. Conclusion; There is an increase in knowledge of cadres about infant massage followed by an increase in skills in terms of baby massage practices and the direct impact experienced by babies, namely increased weight gain and better sleep quality after being massaged every day regularly for 2 weeks.